PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN SUB SEKTOR MINYAK DAN GAS BUMI LISTING DI BEI - Ade Noviyanti Ananda; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of working capital turnover and receivable turnover on profitability in mining company sector oil and gas listed on the Indonesia Stock Exchange period 2009-2014. Independent variable it’s from working capital turnover (X1) and receivable turnover (X2). While used dependent variable (Y) is profitability (ROE and ROI).This study uses secondary data, annual financial statements mining company sector oil and gas listed on the Indonesia Stock Exchange. Sampling was done by sensus sampling the sample used is 7 mining companies sector oil and gas. The analysis technique used is a simple linear regression, multiple linear regression, coefficient determination test, t test, and f test . Data was analyzed by linear regression analysis using software SPSS 21.The results showed that the working capital turnover partially (t test) no significant effect on profitability, and also receivable turnover no significant effect on profitability. The results of simultaneous (f test) showed no significant influence of working capital turnover and receivable turnover on profitability (ROE and ROI).Keywords : WorkingCapital Turnover, Receivable Turnover, Profitability (ROE and ROI)